Status prawny dyrektora szkoły. Zarys problematyki - Pyter, Magdalena (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: The article says about school’s principal legal status. The article consists of the four parts. First part: Indtroduction. Second part: The qualifications to hold the school’s princiapl seat. Third part: Competition. Fourth part: The conclusions close the article. The problem cointained in the article is very serius, because it concerns the issue, which is still actual today.